Adult-onset Still's disease: A great masquerader triggered by hepatitis A infection - Jhasaketan Meher; Keshao B Nagpure; Md Sabah Siddiqui; A M Vishnu Dev (Indian Journal of Rheumatology)
Adult-onset Still's disease (AOSD) is a rare inflammatory disorder of unknown etiology. The varied clinical presentation of the disease mimicking many other diseases makes it difficult to diagnose. Various infectious triggers in a genetically susceptible host have been described in literature. We report a case of a 25-year-old female who presented with fever, rash, and arthralgia and diagnosed to be AOSD triggered by hepatitis A infection after excluding other differentials. She was managed with corticosteroids with dramatic response and continued to be in remission even after steroid withdrawal.